Central bank liquidity auction mechanism design and the interbank market - Kimmo Ollikka; Janne Tukiainen (Bank of Finland, 2013)
We study whether the mechanism design in the central bank liquidity auctions matters for the interbank money market interest rate levels and volatility. Furthermore, we compare different mechanisms to sell liquidity in terms of revenue, efficiency and auction stage interest rate levels and volatility. Most importantly, we ask which mechanism is the best at implementing the target policy interest rates to the interbank market and what are the trade-offs involved. We construct a relatively general model of strategic bidding with interdependent valuations, and combine it with a stylized model of the interbank market. The novel feature of the model is that the expectations of the interbank market outcomes determine the valuations in the liquidity auctions. The model captures the relevant features of how the European Central Bank sells liquidity. We use simulations to compare discriminatory price, uniform price and Vickrey auctions to a posted price mechanism with full allotment. In order to analyze interactions between the primary and the secondary market under four different mechanisms, we need to make a lot of assumptions and simplifications. Given this caveat, we find that posted prices with full allotment is clearly the superior alternative in terms of implementing the policy interest rate to the interbank markets. This comes at the cost of less revenue compared to the revenue maximizing discriminatory price auction, but surprisingly, will not result in efficiency losses compared even to the Vickrey auction.
URN:NBN:fi:bof-20140807175
Keywords: C63; C72; D02; D44; D47; D53; E43; E44; E52; E58; G21; 330; ECB liquidity auctions; Interbank markets; Mechanism design; Multi-unit auctions; Monetary policy; Posted-Prices